Addressing Health Inequities in Energy-Poor Households: Evidence from China’s Photovoltaic Poverty Alleviation Program - Xinyu Yang; Siqi Yu; Xinling Jiang; Ping Jiang (Energies)
Energy poverty, defined as a households’ limited ability to secure affordable energy, has become a key issue in the energy transition debate due to its impact on well-being, health risks, and social inequality. We investigate its health impacts using two-way fixed effects and high-dimensional fixed effects models, two-stage least squares, and quantify additional medical costs during extreme cold events with grouped fitting regression. We assess the effect of China’s Photovoltaic Poverty Alleviation Program using the Difference-in-Differences-in-Differences technique. Our results show that energy poverty significantly worsens household health deprivation, extreme cold events further increase medical costs in southern regions, while northern energy-poor families reduce healthcare spending to cover heating costs, and the Photovoltaic Poverty Alleviation Program significantly reduces both the medical burden and catastrophic medical expenditure among energy-poor households. These findings underscore the need for energy transition policies that combine targeted subsidies, health support during cold seasons, and wider deployment of modern heating technologies to protect vulnerable families and ensure a fair, resilient energy transition.